FACTORS ASSOCIATED WITH MEDICATION ADHERENCE AND SYSTOLIC AND DIASTOLIC BLOOD PRESSURE OF HYPERTENSIVE PATIENTS - Ziddan, Hamka; Ardiana, Meity; Dewanti, Linda; Ratri, Anudya Kartika (Folia Medica Indonesiana, 2025)
Uncontrolled hypertension can cause complications such as heart disease, brain disease, kidney disease, and other diseases. Medication adherence is a primary factor in controlling blood pressure (BP) in hypertensive patients. This study aims to provide an overview of the factors associated with medication adherence of hypertensive patients treated at Taman Public Health Center in Sidoarjo, Indonesia. This study used a cross-sectional approach involving hypertensive patients. This study employed consecutive sampling, with the number of samples comprised of patients undergoing outpatient care from January 2, 2023, to February 25, 2023, totaling 103 respondents. The study employed the Morisky Medication Adherence Scale 8-item (MMAS-8) questionnaire to evaluate medication adherence. Fifty-nine (57.3%) patients had poor adherence, and 83 (80.6%) patients had poor BP control. The significant factors associated with medication adherence were employment status (p = 0.021), drug regimen and prescription refill time (p = 0.001), and experiencing forgetfulness/negligence related to their medication (p = 0.011). Significant factors associated with systolic and diastolic BP are having health insurance (p = 0.030 and p = 0.006) and drug regimen-prescription refill time (p = 0.029 and p = 0.041). These factors can be used as considerations during policymaking to improve medication adherence and BP control of hypertensive patients.